Tax Policy and the Heterogeneous Costs of Homeownership - Bishop, Kelly C.,Dowling, Jakob,Kuminoff, Nicolai V.,Murphy, Alvin (National Bureau of Economic Research, 2023)
The real economic cost of homeownership depends on an intricate system of taxes and subsides that vary over time and across the United States. We incorporate the key features of this system into a framework for measuring the annual user-cost of housing and we use it to document how housing costs and subsidies varied over time, across space, and with household demographics in 2016-2017. Then we examine how the Tax Cuts and Jobs Act of 2017 subsequently reduced subsidies and increased the relative cost of housing. We report how these changes varied by geography, homeownership, race, and voting behavior
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Wohneigentum; Steuerpolitik; Wohneigentumspolitik; USA; Taxation; Subsidies; and Revenue; Household Analysis; Real Estate Markets; Spatial Production Analysis; and Firm Location